The politics of resentment: what is it and how is it mobilized by populist radical right-wing parties in different contexts? - Damhuis, Koen; Rashkova, Ekaterina R. (Frontiers in Political Science, 2024)
The role of emotions in politics is drawing increasing scholarly attention. Yet, despite this heightened interest, the ways in which politicians concretely appeal to emotions of their target audience are still blurry. Let aside how they do so in different contexts. This article focuses on an affect that is frequently mentioned as the key driver explaining the electoral appeal of populist radical right-wing parties (PRRPs): resentment. In that respect, several authors have used the term “the politics of resentment,” even though the exact definition of resentment often remains unclear. In this article, we theorize what resentment precisely is and how it is used politically, and hypothesize how it is mobilized in different ways by PRR parties in different contexts. Empirically, then, we employ content analysis to study a corpus of party documents of PRRPs in three West and two East European countries from 2004 onwards and identify three types of resentment mobilized by the radical right: (1) redistributive resentment; (2) recognitory resentment; and (3) retributive resentment. Despite being expressed in a more heterogeneous way than we theoretically expected, these forms of resentment share important commonalities that, we argue, can help to better understand the electoral appeal of radical right-wing parties.